The effects of public and private investments on food security in Cameroon - Votsoma, Philemon; Albert, Vangvaidi; Pelagie, Pene Zongabiro Nina; Oumarou, Mohamadou; Bruno, Ndouyang Balguessam; Sani, Mohamadou; Hadjara, Bilkissou; Raihanatou, Kaltoumi; Esperance, Fatal; Assana, Abdoulaye (Global Sustainability Research, 2024)
This paper aims to analyse the effects of public as well as private investments on food security in Cameroon. The study, used data from 1988 to 2020 and Generalized Least Squares method for estimation. The results revealed that (i) public investment reduce effect on food security while (ii) private investment has a positive effect on food security. Therefore, the study suggests to Cameroonian government to direct public policies towards investments in agricultural sector in order to boost food production, food availability and food accessibility in the country.